THE INFLUENCE OF AMERICAN ZERO WASTE YOUTUBE VIDEOS ON GLOBAL AND MASSIVE INDONESIAN ZERO WASTE LIFESTYLE AND MOVEMENT - Maria Ardianti Kurnia Sari (Universitas Gadjah Mada, 2019)
Plastic has become a massive problem globally since there is a large portion of the ocean contaminated with plastic waste. Plastic becomes a material that cannot be broken down by soil and takes years to be broken. Therefore, many people try to influence each other to adoptthe zero waste lifestyle as a concern to the Earth. Zero waste has become a global activity that always encourages the society to reduce single-use plastics. Using single-use plastics can be found in everyday life, such as when going shopping to the market, sometimes the sellers will give plastic bag to the buyers. Most of the time, the plastic bag is only used once tobe throwninto the trash can. This research uses qualitative method. The researcher analyzes through zero waste lifestyle videos and books as the primary sources of this analysis. The results of this research are first, the step to get started to become a “zero-waste lifestyler”, second, how to be the “zero waste lifestyler”, and third, how zero waste can give the global lifestyle movement in Bali, Indonesia as their primary program, Bye Bye Plastic Bags, as in June 2019, Bali becomes the first province in Indonesia to ban in using single-use plastics.Keywords: bye bye plastic bags, single-use plastic; zero waste lifestyle